Холмський пам’ятник перемоги поблизу Ярослава 1245 року - Диба, Ю.Р. (Княжа доба: історія і культура, 2015)
Розглянуто літописне повідомлення
1259 р. про холмський стовп з орлом. На
підставі текстологічних вказівок проаналізовано типологічні, морфологічні та
композиційні характеристики холмського стовпа та їхні історичні аналоги. Монумент потрактовано пам’ятником у
вигляді кам’яної колони з базою та чотириликою капітеллю, увінчаним фігурою
орла, встановленим на міському поприщі, призначеному для проведення лицарських
турнірів. Семантичне навантаження композиції холмського монумента з орлом відчитується у трьох знаменнях Ярославської
битви 1245 р. Викладені дають підстави аби вважати, що холмський монумент з
орлом споруджено в пам’ять про цю славетну перемогу Романовичів. There have been considered in the article
the chronicle message of 1259 about pillar with
an eagle, built near the town Kholm. Based on
the analysis of textual instructions, author investigated
typological, morphological and compositional
characteristics of this monument and
its historical counterparts. The monument interprete
das stone column with base and fourfaces
capital, crowned with the figure of an eagle.
This column was set on the city field, intended
for knightlyt ournaments. The semantic content
of the composition of the Kholm monument with
an eagle is encoded in three signs, mentioned in
the article of the Galician-Volynian Chronicl eth
at describes ban le at Yaroslavin 1245. The above considerations givere as ontobelieveth at Kholm
monument with an eagle was erected in memory of this glorious victory.